(untitled) (Communication & Society, 2009)
The spread of television in Spain marked the decline of the official cinema of the Franco regime. So, during last years of Franco, the official film producer, called NO-DO, tried redirected towards the realization of documentary film in colour. After Franco’s death, there were three kinds of NO-DO’s documentaries. Some followed the steps of the new King’s official’s trips. Others, historical documentaries, were aimed at fans of the regime, and contributed to positive memory of Franco. Whereas, in the early years of democratic transition, there are also some documentaries focused on a democratic pedagogy.